2000
DOI: 10.1108/10610420010316302
|View full text |Cite
|
Sign up to set email alerts
|

Internet shopping, consumer search and product branding

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
145
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(153 citation statements)
references
References 18 publications
6
145
0
2
Order By: Relevance
“…Furthermore, individuals with lower income tend to approach online shopping activity more cautiously and find this medium as a riskier place since their tolerance for financial loses is lower with respect to consumers with higher income (Yoldas, 2012). Ward and Lee (2000) found that most online shoppers are male, well educated, younger, and having higher income in a study on the relationship among with Web shopping, brand dependence, and search experiences. Based on the empirical researches, there were two hypotheses that proposed : Lifestyle is a concept defined as the means by which people live and spend time and money, mirroring a person's activities, interest, and opinions, as well as demographic variables (Blackwell, Miniard, and Engel, 2004).…”
Section: B Relationship Between Individual Characteristics and Onlinmentioning
confidence: 99%
“…Furthermore, individuals with lower income tend to approach online shopping activity more cautiously and find this medium as a riskier place since their tolerance for financial loses is lower with respect to consumers with higher income (Yoldas, 2012). Ward and Lee (2000) found that most online shoppers are male, well educated, younger, and having higher income in a study on the relationship among with Web shopping, brand dependence, and search experiences. Based on the empirical researches, there were two hypotheses that proposed : Lifestyle is a concept defined as the means by which people live and spend time and money, mirroring a person's activities, interest, and opinions, as well as demographic variables (Blackwell, Miniard, and Engel, 2004).…”
Section: B Relationship Between Individual Characteristics and Onlinmentioning
confidence: 99%
“…Thus far, research on expert and novice users in the internet context has discussed differences in internet use in general (Hammond et al, 1998), user capabilities, such as internet search performance (Lazonder, Biemans and Wopereis, 2000), impressionability on advertising (Bruner and Kumar, 2000), banner-ad effectiveness (Dahlén, 2001), internet shopping (Ward and Lee, 2000;Martinez-López, Luna and Martínez, 2005), and trust (Corbitt, Thanasankit and Yi, 2003) across different expertise levels. Also, internet user experience has been found to relate as an antecedent to flow-experience on the internet (eg.…”
Section: Expertise and Experience In Internet Contextmentioning
confidence: 99%
“…The ability to collect product information and make comparisons between the different product offerings from different providers is often viewed as one of the main competitive challenges for e-shopping [12]. Online shoppers appear to be attracted to the ease with which they can find information on the Internet, including the detailed product information available and the variety of choices offered [13]. Variety seeking and bargain hunting behaviors can be thus seen as two of the main reasons why consumers shop online.…”
mentioning
confidence: 99%